Designing Human Health Risk Management Model for Dam Construction Projects - R. Ghorbanalipour; AM. Ahmadvand; M. Ahmadvand; H. Eghbali (Salehan Institute of Higher Education, 2018)
Identifying the risks of dam construction projects due to their high importance in terms of utilization, the amount of investment they invest in, the location of the region, the nature of the complexity of the project, and the presence of many uncertainties, including natural disasters and costs High builds are of special importance. Selection and implementation of the project with the least risk can lead to economic savings, optimal use of resources, increased productivity, flood control and supply of drinking water, agriculture and industry. Based on the results of this study, the